2022
DOI: 10.1149/1945-7111/aca838
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials - Poly(3-octylthiophene-2,5-diyl) – Hydrous Iridium Dioxide Triple Composite Materials as Superhydrophobic Layers for Ion-Selective Electrodes

Abstract: In this paper, we introduce a new triple composite material consisting of three significantly different materials: carbon nanomaterial (carbon nanotubes and carbon black), conducting polymer (poly(3-octylthiophene-2,5-diyl), and metal oxide (hydrous iridium dioxide). Combining these three components creates superhydrophobic materials (of contact angle value up to 180). Both designed materials were characterized with high values of electrical capacitance parameters (1.5 and 0.9 mF) and low values of resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, the CNT–polymer nanocomposite is a typical material used in SC-ISEs to increase mechanical stability, alongside flexibility and conductivity. 171,172 Paczosa-Bator et al 173 reported the construction of super-hydrophobic nanocomposite layers consisting of MWCNTs, carbon black, poly(3-octylthiophene-2,5-diyl), and hydrous iridium dioxide for K + determination. Michalska and co-workers 174 developed the MWCNT–poly(3-octylthiophene-2,5-diyl) (POT) nanocomposite as a transducer layer to promote the sensing performance of the electrode for the detection of K + .…”
Section: Applications Of Nanomaterial-based Sc-isesmentioning
confidence: 99%
“…For example, the CNT–polymer nanocomposite is a typical material used in SC-ISEs to increase mechanical stability, alongside flexibility and conductivity. 171,172 Paczosa-Bator et al 173 reported the construction of super-hydrophobic nanocomposite layers consisting of MWCNTs, carbon black, poly(3-octylthiophene-2,5-diyl), and hydrous iridium dioxide for K + determination. Michalska and co-workers 174 developed the MWCNT–poly(3-octylthiophene-2,5-diyl) (POT) nanocomposite as a transducer layer to promote the sensing performance of the electrode for the detection of K + .…”
Section: Applications Of Nanomaterial-based Sc-isesmentioning
confidence: 99%
“…An interesting solution was presented by the authors in article [147], proposing ternary nanocomposites consisting of three types of materials: conductive polymer (poly(3octylthiophene-2,5-diyl)), carbon nanomaterials (carbon black and nanotubes) and metal oxide (hydrated iridium dioxide). The obtained materials were characterized by high hydrophobicity (contact angle up to 180 • ).…”
Section: Composites Based On Polymers and Carbon Nanomaterialsmentioning
confidence: 99%
“…The layer of IrO 2 -POT-MWCNT turned out to be superhydrophobic with a contact angle of 178 • , which resulted in great stability in potentiometric response and long lifetime. This layer was introduced in K + [110] and H + [111] selective electrodes.…”
Section: Metal Oxide Nanoparticles-based Hybrid Materials As Solid-co...mentioning
confidence: 99%